PENGENDALIAN KESELAMATAN DAN KESEHATAN KERJA PADA PROYEK PEMBANGUNAN HOTEL - I Wayan Jawat (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2017)
ABSTRACT The development of equipment technology were used in construction projects must be balanced with skill and high level of risk management, the most appropriate solution by using the safety and health management system so that the assets and labor that is an investment for the entrepreneur can be saved. The issues of occupational safety and health can’t be separated from industry problems, because safety and health are closely related to productivity. Occupational Safety and Health (OSH) in industry are associated with environmental issues. The Ritz Carlton Bali project in Sawangan Nusa Dua is one of the projects undertaken by PT. Tatamulia Nusantara Indah and has ISO certified. The implementation of OSH standards on this project is contained in the OSH plan and is always carried out monitoring and evaluation activities by the safety team in the field. To give more understanding on the implementation of OSH to all project workers was scheduled OSH simulation for 1 (one) hour adjust to schedule of project and informed by safety team, including effort of control that must be done. Based on this, it becomes interesting to do an assessment on OSH Control on Construction Project at The Ritz Carlton Bali Project in Sawangan Nusa Dua. The purpose of this study is to understand the control of OSH on construction projects. The result is a preliminary study was conducted to identify the potential OSH risks of The Ritz Carlton Bali Project. The procedures for reviewing these OSH risks and their system of controls are routinely applied to update hazard and risk records. All important risks are always controlled and monitored. Documented procedures must be available to avoid the delivery of policies and targets. Keyword: planning, labor costs, construction projects